Developing Inclusive High School Team Sports for Adolescents with Disabilities and Neurotypical Students in Underserved School Settings. Issue 2 (28th February 2023) - Clement, Wade; Freeman, Stephanny F N
Abstract: The authors investigated the effects of a collaborative after-school inclusive sports program on adolescents with disabilities and neurotypical students in underserved high schools. The program brought together a large urban school district and a private after-school program to provide a service on the school site. The goals were to provide a truly integrated sports environment for adolescents with disabilities and to provide underrepresented minority students an opportunity to gain service learning, improved social–emotional development, and greater self-perceived impact. The project was feasible and indeed continued well beyond the evaluation period. Quantitative results indicated that the neurotypical adolescents felt they had an impact on improving the responsibility of their peer athlete, and they felt they had better perspective taking after participating. Descriptive comments indicated that the children with disabilities enjoyed participation and that this inclusive program may have provided an additional avenue for a subset of the population to engage more in the activities of their school. Program details are presented to encourage further research and replication.